[OP.5A.05] REDUCED RENAL TISSUE OXYGENATION WITH AGING IN MEN, BUT NOT IN WOMEN. (September 2017) - Pruijm, M.; Milani, B.; Lacoh, C.; Stuber, M.; Burnier, M.
Abstract : Objective: Women are less prone to the development of CKD than men, and their renal function declines less rapidly while aging. Why women are relatively protected remains so far incompletely understood. We hypothesized that renal tissue oxygenation as measured with blood oxygenation level-dependent MRI (BOLD-MRI) is better preserved in ageing women. Figure. No caption available. Design and method: Blood-oxygenation level dependent MR imaging was performed under standardized conditions in respectively 11 young and 11 older healthy women, and also in nine younger and nine older healthy men. All participants were free of medication, and none were hypertensive. Images were analyzed with the twelve-layer concentric objects method (TLCO) that divides renal parenchyma in 12 layers of equal thickness, and reports the mean R2 * value of each layer. The mean R2 * values of all twelve layers can be graphically represented as a curve, that is called the R2 * profile. The estimated glomerular filtration rate (eGFR) was calculated with the CKD-EPI formula (CKD EPI creatinine). Results: The mean(±SD) age of young and older women and young and older men was 36 ± 7 versus 52 ± 6 years, and 35 ± 9 versus 58 ± 8 years; their eGFR was respectively 103 ± 15, 96 ± 9, 97 ± 17 and 89 ± 9 ml/min/1.73m 2 (panova = 0.17) and their body mass index 25 ± 5, 26 ± 6, 26 ± 3 and 27 ± 6 kg/m 2 (p = 0.91). The R2 * profile was shifted to higher R2 * values (corresponding to lower oxygenation) at increasing age in men, but not in women (see figure). Conclusions: These data show that renal tissue oxygenation is well maintained while aging in women, but not in men. This finding offers clues to the underlying mechanisms responsible for the relative nephroprotection observed in women. Whether hormonal, hemodynamic or structural differences are responsible for the better preserved renal oxygenation in women needs further study.